Implement biometric authentication of users enhancement model and algorithm research - Avezov Erkinjon Sherimmatovich; Bekchanov Faxriddin Atabekovich; Boburbek Babajanov Farhodovich; Musayeva Mukhtasar Zayirjon qizi (Genius Journals, 2022)
This article analyzes the importance of biometric authentication, which is currently evolving, to ensure information technology and security
Keywords: Authentication; identification; fingerprints; password